Do cage fish farms interfere with the food aspects of the wild species Metynnis lippincottianus (Characiformes, Serrasalmidae)? - Ramos, Julia Kaori Kuriyama [UNESP]; Do Bonfim, Vinicius Cesar [UNESP]; Kliemann, Bruna Caroline Kotz [UNESP]; Garves, José Daniel Soler [UNESP]; Delariva, Rosilene Luciana; Ramos, Igor Paiva [UNESP] (Boletim do Instituto de Pesca, 2022)
We evaluated the differences in the diet and trophic guild of Metynnis lippincottianus under the influence of cage fish farms in the Neotropical reservoir. We collected samples from two areas (cage farm and control) in March and June 2019. Stomach contents were examined, and food items were identified and quantified using the volumetric method. Differences in diet composition were evaluated using PERMANOVA and SIMPER analyses, while trophic niche breadth was determined using PERMDISP. The trophic guild for each area was also determined. Significant differences in diet between cage farm and control areas were observed, due to consumption of pelleted feed, mi-crocrustaceans, Egeria sp., and filamentous algae. In both sampling areas, M. lippincottianus was classified as algivorous. Despite the pelleted feed consumption in the cage farm area, no differences were observed in trophic niche breadth and the trophic guild. In addition, algae and macro-phytes still accounted for the majority of this species’ diet in both areas, indicating partitioning of resources. This resource partitioning may favor coexistence, but it is worth mentioning that pelleted feed consumption still indicates the influence of cage fish farms on the diet of wild fish.
Pisciculturas em tanques-rede interferem sobre os aspectos alimentares da espécie silvestre Metynnis lippincottianus (Characiformes, Serrasalmidae)?
Keywords: aquaculture; environmental impact; non-native species; pacu-prata; pelleted feed; trophic guild